2015
DOI: 10.3390/fib3040491
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Analysis of Repaired Masonry Elements with Flax-FRCM and PBO-FRCM Composites Subjected to Axial Bending Loads

Abstract: Abstract:In the construction industry, the use of natural fabrics as a reinforcement for cement-based composites has shown great potential. The use of these sustainable composites to provide strengthening or repair old masonry structures that exhibit structural problems mainly due to a poor tensile strength of the mortar/brick joints is revealed to be a promising area of research. One of the most significant load conditions affecting the mechanical response of masonry structures occurs when axial bending loads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 29 publications
1
5
0
1
Order By: Relevance
“…In a comparative study between PBO and flax lime-based TRM, Olivito et al [54] observed through double-lap test that bond stress [50] values of flax composites are similar to the ones of PBO, which indicated that PBO fibers exploited less than 30% of their mechanical capacity unlike flax fibers. Moreover, the progressive cracking detected with flax-TRM demonstrated better ductile behavior than PBO that had a sudden delamination, see Figure 10, which is concordant with what other studies reported [43] [44].…”
Section: Tensile and Bonding Behavior Of Nfcssupporting
confidence: 89%
See 1 more Smart Citation
“…In a comparative study between PBO and flax lime-based TRM, Olivito et al [54] observed through double-lap test that bond stress [50] values of flax composites are similar to the ones of PBO, which indicated that PBO fibers exploited less than 30% of their mechanical capacity unlike flax fibers. Moreover, the progressive cracking detected with flax-TRM demonstrated better ductile behavior than PBO that had a sudden delamination, see Figure 10, which is concordant with what other studies reported [43] [44].…”
Section: Tensile and Bonding Behavior Of Nfcssupporting
confidence: 89%
“…That conclusion was reliant on the higher strength attained (more than 25% over PBO-strengthened walls), higher ultimate strains and absence of debonding if compared to PBO-TRM. Another concordant results, considering the study of [44], assured that the capacity of flax-FRCM to transfer the loading to the substrate to release the stored energy, is a preferential aspect that highlights their compatibility to repair damaged masonry. Additionally, the higher bending moment under eccentric loading, good deformability and the ability to restore stiffness might extend the possibility of applying this repairing system to different kinds of loads [43] [44].…”
Section: Mechanical Improvements Of Structural Components Strengthenementioning
confidence: 84%
“…Such beams allow overcoming many of the now well-known problems that were recognized to be due to r/c beams. This strengthening system was recently studied in some researches by other Authors [42][43][44][45][46], while the validation of this reinforcement solution for masonry beams was verified by experimental tests on full-scale beams reinforced by glass fiber-reinforced polymer composite [28]. Several specimens were tested under cyclic flexure and long duration loading.…”
Section: Masonry Ring-beams Reinforced By Natural Fibersmentioning
confidence: 93%
“…The assumption regarding the bond between bricks and fiber reinforced cementitious matrix composite materials is a well-established hypothesis for this reinforcing technique, and is also based on excellent results achieved in experimental researches. In Codispoti et al [34], Cevallos et al [46] and Olivito et al [54] it is shown that flax fiber reinforced cementitious matrix have a good bond behavior with the masonry support; it is also shown how flax fibers made full use of their mechanical properties in the composite during the tests performed.…”
Section: Methodsmentioning
confidence: 98%
“…Figura 2.7. Colocación del FRCM [11] Las dos principales aportaciones que realiza la matriz al material compuesto son la conexión entre el material substrato a reforzar (mampostería) y la malla, y la protección de la fibra frente a las condiciones externas (humedad, luz solar, etc.). La primera aportación es la más relevante a nivel estructural puesto que el FRCM únicamente contribuirá a soportar las cargas que la matriz sea capaz de transferir desde la superficie de la mampostería a reforzar hasta las fibras.…”
Section: Refuerzo De Mampostería Con Frcmunclassified